일제강점기 저항시의 '주체' 연구 - 박옥실 (The Graduate School, Ajou University, 2009)
<국문초록> 본 논문의 목적은 1930년대 중반 저항시에 나타난 주체 개념을 중심으로 작품에 내재된 주체의 양상을 규명하고자 하는 데 있다. 이육사, 이용악, 윤동주가 일제 통치 강화시기에 저항의식을 바탕으로 창작활동을 하였다는 데 주목하고 이들이 가진 공통적 시대배경 아래 근대적 주체가 어떻게 형성되고 확립되었는지 살펴보았다. 각 주체의 변별성이 각각의 작품에 어떻게 드러나는지 파악하고자 하는 것은 비슷한 시기에 창작활동을 했지만 이들 시인이 경험한 외부적 요인이 각각 달랐고 경험한 정신세계가 달랐다는 데 충분히 연구할 가치가 있다고 판단했기 때문이다. 본 논문은 저항시의 자아를 근대적 주체로 상정하고 세 시인이 경험한 정신세계와 타자와의 관계가 역사성을 갖고 서로 맞물려 있다는 데서 특별한 의미를 갖는다고 보았다. 이러한 주장을 뒷받침하기 위해 헤겔의 『정신현상학』에서 자기의식에 기초한 개별자가 인륜적 실체로 나아가기 위해 어떠한 변증법적 과정을 거치고 있는지 관련시켜야 한다. 주체가 주체이기 위해서는 인간을 가장 인간이게 하는 ‘자유’가 필요하다. 인간이 사유하지 않는다면 자유도 ‘자유’일 수 없다. 인간이 사유하기 때문에 자유로이 타자와 관계하며, 타자에 머물러 있지 않고 타자로서의 존재자를 포괄하여 타자 속에서 주체를 인식하게 된다. 즉자에서 대자로 이르는 과정에서 개인은 자기 자신이 누구인가를 깨달으며 인식하고 개인으로서 주체가 되어야 한다. 그래야만 ‘나’와 사회 속의 ‘나’, 민족으로서의 ‘나’를 체험하게 되고 이러한 행위를 통해 보편성을 획득한다. 그러나 주권이 침탈되고 자유를 속박 당한 식민지 하의 주체는 강제로 체제에 순응하거나 삶의 터전에서 내몰려 결핍과 갈등에 내던져진다. 이들 세 시인은 이러한 상황아래 ‘나’의 ‘나’ 됨에 대한 철저하고도 실존적인 자각을 한다. 자신의 주체적인 삶, 주인된 삶을 살고 싶은 욕망을 욕구하는 것이다. Ⅱ장에서는 헤겔의 『정신현상학』의 이론을 기반으로 주체와 시대인식의 문제를 살펴보았다. 이것을 토대로 주체의 개념과 일반론적인 주체의 양상을 살펴보고 억압적 현실에서 주체는 또 어떻게 드러나며 대응하는지 파악하였다. 또한 식민시대의 국권 상실과 좌절, 억압을 경험한 주체는 주관적 반성을 통하여 대립과 분열을 자초하나 스스로 점진적인 상승과정을 거쳐서 회복을 꿈꾸며 자기의식 주체에 다다름을 살펴보았다. 이들은 각기 다른 세계인식과 경험을 작품에 반영하며 개인에서 근대적 주체로 변모한다. 헤겔의 주인과 노예의 변증법은 이를 증명한다. 자기의식은 서로간의 투쟁에서 승리하고 자유와 자립성을 획득하는 자기의식의 형태가 될 때 주인이 되며, 노예는 이 투쟁의 결과에서 지는 타자, 즉 굴복과 예속에 떨어지는 노예가 된다. 이러한 인정투쟁의 결과 노예는 자기의 욕구가 아니라 주인의 욕구를 위해 노동하고 주인은 노예의 노동에 의해 그 자립성이 부정된 노동 산물로 자신의 욕구를 충족하게 되는 것을 의미한다. 그러나 합리적인 사회관계가 성립되기 위해서는 개인과 개인, 개인의 삶과 공적인 삶이 유기적으로 통일되어야 하고 자기정체성을 확보하여야 한다. 본 논문에서 이육사, 이용악, 윤동주의 주체성 확립은 이러한 맥락에서 검토되어야 한다고 보고 각각의 변별성을 구체적으로 파악하였다. Ⅲ장에서는 이육사가 인식한 식민지 현실에서 주체가 세계와 어떻게 대응하고 소통하고 있는지 살펴본다. 개인의 삶과 경험의 산물이 어떻게 작품에서 시적으로 승화되었는지 전기적 측면에서만 치우치지 않고 독자적이고 개성적인 주체에 입각하여 작품에 접근하였다. 그에게 형성된 저항은 단지 물리적이고 기능적 시간에서 존재하는 것이 아니다. 개인에서 민족의 수탈을 경험하며 현실적 자아와 시적 자아의 반복되는 갈증과 갈등으로 변모되며 식민지 현실과 대립되는 양상을 보인다. 또한 주체는 희생제의의 비극적 운명을 인식한다. 주체가 세계에서 인식의 대상으로 삼는 사물과 이미지는 초월적이고 우주적이며 직정적이다. 작품에 표상된 낭만은 현실을 몽환과 몽상으로서의 낭만이 아니다. 어디까지나 현실의 서정으로 현현되고 승화되었음을 살폈다. Ⅳ에서는 민족소명의식과 민중적 주체를 드러낸 이용악을 살펴보았다. 향토성이 짙은 삶의 배경과 가난과 유랑으로 점철된 시인은 가난한 지식인의 전형을 가졌다는 데서 이육사와는 다른 양상을 보인다. 전기적 사실과 작품에서 드러난 세계인식은 리얼리즘이라는 직접화법의 양태를 보이며 현실과 작품의 이원적 공간을 자유로이 넘나들게 된다. 이러한 과정에서 주체는 ‘나’에서 ‘우리’라는 민중적 자아로 확인된다. 민중적 삶과 연대적 양상을 보이는 작품의 서사적 요소는 트라우마로 나타난다. 갈망과 지향의지가 크면 클수록 이상세계는 더욱 멀어진다. 그러나 이때의 체험은 자연 이미지의 소재나 시적 주제에 의해서 저항적 요소를 표출하게 된다. 풍요에의 지향은 남쪽이라는 상징적 방향을 제시하며 실존적 탐색을 모색하였다. Ⅴ에서는 윤동주의 초극의지와 내면적 주체의 양상을 살펴보았다. 윤동주는 이육사와 이용악과는 또 다른 현실적 배경을 갖고 있다. 이러한 이유로 인해 그는 뿌리내리지 못한 결핍된 주체로 표출된다. 그가 인식한 세계는 상실과 결핍과 소외 그 자체다. 민족의 동질감마저 ‘함께’, ‘늘’하지 못한다는 결핍의식으로 이어진다. 이국땅을 고향으로 삼고 그 터전 위에서 민족의식과 고향의식이 굴절된 형태로 이루어졌다. 따라서 윤동주의 주체는 타민족의 정서 속에서 정체성의 모호함이라는 주체적 자아로 놓인다. 상실의 공간에서 생래적인 고향과 이상적인 고향을 꿈꾸며 끊임없이 ‘나’를 성찰한다. 이때 현실과 내면의 틈바구니에서 자아의 인식세계는 반성에서 화해와 모색을 가져온다. 개별적인 주체가 사회인륜적인 주체로 확장되고 또한 근대적 주체로서 기능하는 것은 어디까지나 ‘나’라고 하는 개별자인 주체가 보편자로서 ‘나’로 이행될 때 가능하다. ‘나’가 어떻게 사회인륜적인 주체가 될 수 있는가는 자유와 시대적 과제가 필연적으로 따른다. 본질적으로 자유로운 인간은 억압된 상황을 놓이게 되면 필연적으로 저항을 동반한다. 그간 한국은 역사를 제대로 세우지 못한 수동적 상태였다. 그러나 개인과 민족 그리고 이데올로기의 사상적 조류에 휩쓸린 세 시인의 근대인식은 각기 다른 방법을 통해 주체인식을 하게 하였다. 주체는 갈등과 소외와 상처를 인식하면 할수록 개별자에서 보편적 주체로 나아가는 역동성을 보였다. 그간 이육사, 이용악, 윤동주의 저항시를 한 곳에 놓고 주체를 고찰한 경우가 없었으나 개인의 성찰과 저항을 기저에 놓고 인간 본연의 자율성에 기초한 ‘저항시의 주체확립’ 은 문학사적 의의를 새롭게 했다. 진정한 자유인(주체)의 모습은 지배와 예속의 틀에서 자유와 평등을 진정으로 원하고 실천할 때 발현된다. 주요어 : 주체, 근대적 주체, 자기의식, 자유, 타자, 보편성, 주인과 노예, 사유, 공간, 고향, 개인, 민족의식, 저항 --------------------------------------------------------- This study aims at figuring out aspects of subjects embedded in resistant poetries in the mid-1930s. It also focuses on the subjective ideas embodied in the works. With an emphasis on their activities based on resistance against Japanese imperial rule, this study considered how modern subjective idea has established by Lee, Yuk-sa, Lee, Yong-ak, and Yoon, Dong-ju. Their differences are singled out in this study since it is thought to be worthwhile to study their distinguished experiences and ideas stemming from their different external factors. This study sees the egos of the resistant poetries as modern subjects. It has found that the resistant poetries have special implications in a sense of combined the poets' spirits with their relations with others based on historicity. To support these arguments, it is necessary to find out what kinds of dialectic process the entities of self-consciousness have went through to come closer to a moral entity from the perspective of Hegel's Phänomenologie des Geistes. For a subject to be itself, "freedom" that enables human beings to be themselves is necessary. If human beings do not think, freedom cannot be itself. Since human beings think, they are free to make relations with others, and they are able to recognize themselves among others including the idea of themselves as others. On the process, an individual find and recognize who him- or herself is and should become a subject. Then, one can experience him- or herself, him- or herself in society, and him- or herself as an entity of a nation. The recognition and experiences lead to his or her winning of universality. However, the subject is deprived of his or her sovereignty with his or her freedom restricted under the colonial rule. The dire situation force the subject to go with the tide, otherwise he or she will be left behind in want and conflict. The three poets make thorough, existent recognition about what makes "ego" as it is: craving for desire of living a subjective life. In the second chapter, questions of subject and recognition of the times are considered based on Hegel's Phänomenologie des Geistes. On the top of it, the definition and patterns of subject in general have been considered, and it has been figured out how a subject is revealed in a oppressive reality. In addition, it has been found that a subject who has witnessed the loss of his or her nation's sovereignty and subsequent frustration under the colonial rule leads to having conflicting identities, but they increasingly restore what they are and come closer to a sense of sovereignty. Each poet reflects his own world view and experience in their poetries and turns into a modern subject. The Hegelian dialectic proves it. When self-conscious gains victory and wins freedom and independence, it becomes a subject; while when it loses in the conflict it becomes object, which is equivalent to a servant. Such a servant does not work for him- or herself, but for their masters, and their masters fulfill their desires with the results of the servants' labor that lacks independence. However, to establish a reasonable social relationship, individuals and their personal and official lives should be combined, and they should secure their self-conscious. In this study, the three poets' establishments of subjectivity are considered on such context, and their differences are singled out. In the third chapter, it considers how a subject that perceived by Lee, Yuk-sa deals and communicates with the world in the colonial rule. Apart from a biased, biographic approach that focuses on how the poet's life and experienced are embroiled in the poet, an approach from the perspective of an independent and individual subject has been taken. To Lee, resistance does not exist in a mere physical, functional time. It takes a form of transition into identical conflicts caused by experiencing exploitation of one's nation, which is antagonistic against the reality of colonial rule. Furthermore, the subject recognizes the tragic destiny. The things and images that the subject recognizes are transcendental, universal, and static. The romance embodied in the poet is not a romance as fantasy: as far as romance is concerned in this poet, it is revealed and sublimated as lyricism of reality. In the fourth chapter, it considered Lee, Yong-ak's sense of national manifest destiny and people's subject. He was born and lived in Korea and in poverty, which fact is distinguished from Lee, Yuk-sa in a sense that his life was the prototype of a poor intellectual. His life history and world view revealed in his poetries takes the form of realism, standing above both the reality and his works. On the course the subject is founded to be a popular identity from "myself" to "ourselves". The epical factor that takes the form of popular life and the feeling of solidarity is revealed as a trauma. The more desires and directivity he has, the farther the ideal world fades away. However, such experience is revealed as resistance by natural images and poetic themes. The aim at abundance represents the symbolic direction of South and makes a existent journey. In the fifth chapter, it considered Yoon, Dong-ju's will of conquest and patterns of inner subject. He has different background, distinguished from Lee, Yuk-sa and Lee, Yong-ak. This is the reason why he is revealed as a subject that has failed to settle down. He recognized the world as loss, want, and alienation, which leads to a sense of "permanent" lacking of national identity. He was born in a foreign country, where he formed his sense of nationality in a modified manner. As a result, his subject is a subjective self-conscious with identical ambiguity in the sense of estrangement. In the place of loss, he dreams about natural and ideal home with incessant self-reflection, when he takes reconciliation of self-conscious from the crack of reality and conflicting identity. An individual subject can be extended to become a social, moral subject and to play a role as a modern subject only when "I" as an individual is transformed into "I" as a universal. It requires freedom and the spirit of the times. A man, by himself, is free, so if he is under oppression, it is natural for him to show resistance. By far, Korea has been in a passive situation, in which it has never made its historical view right. However, the three poets' modern awareness of individual, nation, and ideological tides enabled Korean people to recognize themselves as a subjective in different ways. The subject has shown activity, with which he comes closer to a universal subject apart from an individual one as he further awares of conflicts, alienation, and hurts. Given that there has never been a comprehensive study on Lee, Yuk-sa, Lee, Yong-ak, and Yoon, Dong-ju, this study is an original and meaningful attempt in the history of literature study in a sense that it considered the "establishment of subjects of resistant poetries" based on a human being's natural autonomy with self-reflection and resistance. Real freedom of a man can be embodied when he really desires and actualizes freedom and equality under oppression and restriction. Key Words : subject, modern subject, self-conscious, freedom, others, universal, masters and slaves, thinking, place, home, individual, national identity, resistance
학위논문(박사)--아주대학교 일반대학원 :국어국문학과,2009. 2
Keywords: 주체; 근대적 주체; 자기의식; 자유; 타자; 보편성; 주인과 노예; 사유; 공간; 고향; 개인; 민족의식; 저항